Hubungan Antara Pembelajaran Berbasis Kesetaraan Gender dan Komunikasi Interpersonal Dengan Efektivitas Pembelajaran di SMAN Wilayah Kecamatan Pasar Minggu - Annisa Tanzilah; Ihsana El Khuluqo; Ade Hikmat (CV. Creative Tugu Pena, 2024)
Education is expected to be a platform for fostering gender equality, where every individual has equal opportunities to develop and fully participate in the learning process. The main objective is to determine whether gender equality-based learning processes and interpersonal communication influence learning effectiveness. This research employs a quantitative method with a descriptive analysis approach. The sampling technique used is saturated sampling. The researchers focused on high school teachers in the Pasar Minggu district. Data were collected from 71 out of 250 teachers using the Slovin formula with a significance/error rate of 0.1 or 10%. The results of the study indicate that the gender equality-based learning variable does not have a significant relationship with learning effectiveness, as the t-value is smaller than the t-table value (0.516 < 1.295). The criteria for a significant relationship are that the t-value must be greater than the t-table value, significant at 0.608 > 0.1, with a significance criterion of sig < 0.1. Meanwhile, the interpersonal communication variable is said to have a relationship because the t-value is greater than the t-table value (3.583 > 1.295) and the significance value is 0.001 < 0.1, meeting the significance criteria. Therefore, it can be concluded that gender equality-based learning does not have a relationship with learning effectiveness, but interpersonal communication does have a relationship with learning effectiveness.